Hunter-Gatherer Occupation of the Central Colorado Plateau during the Pleistocene-Holocene Transition. Issue 3 (July 2020) - Tune, Jesse W.
Abstract : The central Colorado Plateau contains an exceptional density of cultural resources. Historically, however, archaeological investigations have overlooked the late Pleistocene and early Holocene record of this region. As such, there is currently a biased understanding of the earliest human occupations and adaptations. The regional Paleoindian record is reviewed here to assess the nature of initial human occupation of the area. Projectile point typologies, toolstone selection, and site distributions are used to characterize the land use patterns used by the region's earliest inhabitants. Results suggest that as early as circa 13, 000 cal BP Clovis groups were familiar with the lithic landscape and habitually made use of local materials. Subsequent Paleoindian populations maintained relatively consistent levels of occupation throughout the Pleistocene-Holocene transition. Finally, the presence of classic Southwest, High Plains, and Great Basin–related lithic technologies suggests that the central Colorado Plateau was part of early interregional land use strategies.